Evaluation of anticancer activity of momordica balsamina extracts and potential interactions with a conventional anticancer drug in colon cancer - Malemela, Kholofelo Mmanoko (My University, 2021)
Cancer remains one of the leading causes of morbidity and mortality worldwide with an estimated 9.9 million deaths in 2020. Cancer treatment regimens such as chemotherapy and radiotherapy have over the years fallen short due to drug resistance, toxicity, damage to normal healthy cells and tissues surrounding the treatment area. Moreover, they have shown very limited survival benefits for most advanced staged cancers such as colorectal cancer, which in 2020 was responsible for 3 728 deaths with a 6.8% incidence rate. Despite the many efforts in developing alternative chemotherapeutic strategies, cancer of the colon and cancer, in general, remains a burden. For centuries, plants and plant derivatives have been exploited for their nutritional and medicinal properties and now serve as chemical scaffolds or templates for designing and synthesising products with pharmacological importance. Herbal medicines are claimed to enhance therapeutic effects and are often used in combination with chronic medication. However, the concurrent use of herbal medicines and synthetic drugs may affect the pharmacokinetic profile of therapeutic drugs or trigger unexpected and undesirable effects. This study aimed to characterise the leaf extracts (crude water and crude methanol) of Momordica balsamina and investigate their potential anticancer activity on HT-29 colon cancer cells. The study also aimed to asses the effect of the extracts on drug metabolising enzymes (CYP450), specifically those which metabolise 5-Fluorouracil (5-FU) prodrugs or are inhibited by 5-FU since it is one of the first-line treatments for colon cancer. Dried powdered leaves were extracted using water and absolute methanol to obtain crude water and crude methanol extracts, respectively. For characterisation, the extracts were spotted on thin-layer chromatography (TLC) plates and further screened using chemical tests. The ferric ion reducing power assay and Liquid chromatographymass spectrometry were used to determine the antioxidant activity of the extracts and to identify prominent or abundant compounds in each extract, respectively. To assess the cytotoxic effect of the extracts and 5-FU, HT-29 colon cancer cells and C2C12 muscle cells, which were used as a model for normal cells, were exposed to concentrations that ranged from 0 to 2000 µg/ml for the water (H2O) extract, 0 to 300 µg/ml for the methanol (MeOH) extract or 0 to 100 µg/ml of 5-FU for 24 and 72 hours, and subjected to the MTT assay. The effect of the extracts on the efficacy of 5-FU was xxi assessed using the MTT assay by combined treatments of the extract and 5-FU. Genotoxicity of the extracts was assessed on the C2C12 cells using the Muse™ MultiColour DNA Damage kit. The generation of intracellular reactive oxygen species (ROS) was assessed by flow cytometry using the DCFH-DA assay. The JC-1 and acridine orange (AO)/propidium iodide (PI) staining assays were used to assess the effect of the extracts on the mitochondrial potential as well as cell and nuclear morphology, respectively. Apoptosis was quantified by flow cytometry using annexin V/PI and caspase activation assessed using the Caspase-8 and Caspase-9 colourimetric assay kits. The pro-apoptotic mechanism(s) was determined by assessing the expression profiles of selected apoptosis regulatory proteins using the human apoptosis antibody array kit. Cell cycle analysis by flow cytometry was conducted to determine the effect of the extract on the cell division cycle. Moreover, to determine the potential of herb-drug interactions, the Vivid® CYP450 Screening kits and P-gp-GloTM Assay Systems with P-glycoprotein were used to assess the effect on the activity of drug metabolising enzymes and drug transportation, respectively. The results showed that the MeOH extract possessed fewer polar compounds, higher ferric iron-reducing power, and a relative abundance of flavonol glycosides, cucurbitane-type triterpenoid aglycones, and cucurbitane-type glycosides than the H2O extract. The MeOH extract was further selectively cytotoxic to the HT-29 colon cancer cells at 24 hours of treatment and selectively induced genotoxicity in HT-29 cells. The H2O extract, however, was not cytotoxic to the HT-29 cells at all the tested concentrations at 24 and 72 hours of treatment. Analysis of nuclear and cell morphology suggested that the decrease in the percentage viability of MeOH extracttreated cells was associated with apoptotic cell death. Apoptosis was further confirmed by the loss of mitochondrial potential, increase in ROS production, caspase-8 and -9 activities as well as Annexin-V/PI-stained cells. Cell cycle analysis revealed cell cycle arrest at the S phase in MeOH extract-treated cells. Analysis of protein expression profiles revealed that the extract modulated various proteins that play a role in the promotion or inhibition of apoptosis. Moreover, the MeOH extract was shown to inhibit the activity of CYPs 1A2, 2A6, 2C8, and 2C9, while the H2O extract showed no significant inhibitory effects on the activity of all tested CYPs and 5-FU only significantly inhibited the activity of CYP2C9. However, combinatory treatments with 5-FU and the MeOH extract were shown to have no additive or diminishing effects on the efficacy of 5-FU on the activity of all the tested CYP enzymes. Treatment with 5FU (0.008 – 32 μg/ml) and the H2O extract (0.02 – 200 μg/ml) was shown to stimulate the ATPase activity of P-gp, while the MeOH extract significantly inhibited its activity with concentrations of 0.2, 2, and 20 μg/ml. In conclusion, the MeOH extract selectively induced cancer cell toxicity, genotoxicity as well as S phase cell cycle arrest and apoptosis via the intrinsic and extrinsic pathways. The anticancer activity of the MeOH leaf extract of M. balsamina as well as its antioxidant potential may be attributed to the presence and relative abundance of flavonol glycosides, cucurbitane-type triterpenoid aglycones, and cucurbitane-type glycosides. Although the MeOH extract may potentially reverse the effects of P-gp multidrug resistance by decreasing its activity, its inhibition of the activity of CYPs 1A2, 2A6, 2C8 and, 2C9, which are involved in the metabolism of more than 80% of the drugs in clinical use may suggest that co-administration of the MeOH extract may still result in increased plasma levels of drugs, thereby resulting in toxicity. The H2O extract, although not pro-apoptotic as the MeOH extract may still have the potential to be developed as a nutraceutical as it was shown to exhibit no adverse drug interactions and because this species is known to possess a wide variety of nutritional and medicinal values.
Thesis (Ph.D. (Biochemistry)) -- University of Limpopo, 2021
Keywords: Anti-Cancer.; Colon Cancer.; Momordica Balsamina.; Treatment.; Cancer; Colon (Anatomy) -- Cancer; Cancer -- Chemotherapy; Medicinal plants -- South Africa; Momordica; Cancer -- Radiotherapy